Influencing Change: When “Best Practice” Changes and the Prototypical Good Farmer Turns Bad - Green, Laura; Kaler, Jasmeet; Liu, Nicola; Ferguson, Eamonn (Frontiers in Veterinary Science, 2020)
Twenty-nine farmers with a flock prevalence of lameness >5% were visited in 2013. They participated in a facilitated discussion on treatment of footrot, and evidence-based new “best practice.” One year later, farmers were revisited and management and motivators for change were discussed. Farmers were asked how they would persuade other farmers to adopt “best practice.” Initially, most participants were resigned to having lame sheep. They believed that prototypical “good farmers” (including trusted family) practiced foot trimming, the traditional “best practice” and that the new “best practice” would be expensive and time consuming. Between 2013 and 2014 lameness prevalence reduced from 7.6 to 4.3%. The major behavioral changes were reduction in foot trimming, increased use of antibacterials to treat footrot, and treating sheep within a week of becoming lame. In 2014, participants were re-interviewed. They reported that an increased knowledge of the evidence-base, trust in the facilitator and talking to other trusted farmers who had already adopted the new “best practice” overcame concerns about the prototypical “good farmer” and motivated change. Persistent change occurred because participants observed health benefits for their sheep and that the new “best practice” had saved time and money. Participants stated that other farmers would be convinced to change to the new “best practice” because it saved time and money, ironically, these were among the original barriers to change. This is possibly an example of cognitive dissonance because farmers had become positive about the benefits of saving time and money following a change in their own behaviors.